Exogenous Nitric Oxide Up-regulates the Runx2 Via Bmp7 Overexpression to Increase the Osteoblast Matrix Production In Vitro - Mohammad Hussein Abnos; Javad Sargolzaei; Mahsa Maleklou (Avicenna Journal of Medical Biochemistry, 2022)
Background: Nitric oxide (NO) is a signaling molecule that is required for the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). According to previous reports, high concentrations of sodium nitroprusside (SNP) inhibit the osteogenic differentiation of BMSCs, while its low concentration promotes this process.